2018
DOI: 10.1080/14786419.2018.1428601
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-MS/MS and cytotoxic activity of three Pistacia species

Abstract: LC-ESI-MS/MS was used for a comprehensive characterisation of ethanol extract from the leaves of three Pistacia species. After optimisation of the method and the use of the negative ionisation mode, a total of 42 different compounds were identified, of which 22 were tentatively characterised in P. chinensis Bunge, 33 in P. khinjuk stocks and 25 in P. lentiscus L. leaves. Flavonoids, phenolic acids, and their derivatives were the most abundant identified compounds. LC-ESI-MS/MS revealed identification of 15, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Some studies ( Table 3 ) aimed to evaluate the anticancer potential of different phenolic extracts of this plant in vitro. The ethanolic leaf extracts showed anticancer potential against lung cancer A549, breast cancer MCF7, prostate cancer PC3, and HepG2 liver cancer in vitro [ 45 ]. Yemmen et al (2017) [ 60 ] revealed the anti-proliferative activities of leaf hydro-methanolic extracts against two human neuroblastoma cell lines (SK-N-BE(2) C and SH-SY5Y) with IC50 values of 100 μg/mL and 56 μg/mL, respectively.…”
Section: Prominent Pharmacological Activitiesmentioning
confidence: 99%
“…Some studies ( Table 3 ) aimed to evaluate the anticancer potential of different phenolic extracts of this plant in vitro. The ethanolic leaf extracts showed anticancer potential against lung cancer A549, breast cancer MCF7, prostate cancer PC3, and HepG2 liver cancer in vitro [ 45 ]. Yemmen et al (2017) [ 60 ] revealed the anti-proliferative activities of leaf hydro-methanolic extracts against two human neuroblastoma cell lines (SK-N-BE(2) C and SH-SY5Y) with IC50 values of 100 μg/mL and 56 μg/mL, respectively.…”
Section: Prominent Pharmacological Activitiesmentioning
confidence: 99%
“…In cell culture studies, mastic gum resin has shown anticancer effect in bile duct cancer (cholangiocarcinoma) (KMBC), pancreatic carcinoma (PANC-1), gastric adenocarcinoma (CRL-1739), and colonic adenocarcinoma (COLO205) cells [ 112 ]. P. lentiscus extract showed moderate activity against liver cancer [ 113 ] as well as breast cancer [ 114 , 115 ]. Raw and roasted pistachio showed a chemo-preventive potential regarding colon cancer [ 116 ].…”
Section: Health Benefits Of Pistachio Consumptionmentioning
confidence: 99%
“…Seven organic acid derivative compounds were identified by LC-QTOF-MS in the aqueous-alcoholic extract of P. (21,24,(26)(27)(28). Table 2 shows detailed information about the data of the molecules and fragments.…”
Section: Lc-qtof-ms Analysis Of Crude Extractmentioning
confidence: 99%